Proteomic analysis of naturally occurring boron tolerant plant Gypsophila sphaerocephala L. in response to high boron concentration - Tombuloglu, Huseyin; Tombuloglu, Guzin; Sakcali, Mehmet Serdal; Turkan, Ali; Hakeem, Khalid Rehman; Alharby, Hesham F.; Fahd, Shah (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
Gypsophila sphaerocephala is a naturally Boron (B) tolerant species that can grow around the B mining areas in Turkey, where the B concentration in soil reaches a lethal dose for plants (up to similar to 8900 mg kg(-1) (similar to 140 mM). While its interesting survival capacity in extremely B containing soils, any molecular research has been conducted to understand its high tolerance mechanism yet. In the present study, we have performed a proteomic analysis of this plant to understand its high tolerance towards B-stress. Seedlings of G. sphaerocephala were collected from B mining area and were adapted to greenhouse conditions. An excessive level of Boric acid (3 mM) was applied to the plantlets for 24 h. Total proteins were precipitated by using TCA/Acetone method. 2D-PAGE (two-dimensional polyacrylamide gel electrophoresis) analysis of the proteins was carried out. Out of 121 protein spots, 14 were differentially expressed between the control and B-exposed G. sphaerocephala roots. The peptide profile of each protein was determined by MALDI-TOF mass spectrometer after in-gel trypsin digestion. The identified proteins are involved in different mechanisms in the cell such as in antioxidant mechanism, energy metabolism, protein degradation, lipid biosynthesis and signaling pathways, indicating that G. sphaerocephala has multiple cooperating mechanisms to protect itself from high B levels. Overall, this study sheds light on to the possible regulatory switches (gene/s) controlling the B-tolerance proteins and their possible roles in plant's defense mechanism.
Keywords: Boron; Gypsophila; Hyper-accumulation; Proteomics; 2D-PAGE; Maldi-TOF